Identification of sand frogs (Anura: Pyxicephalidae: Tomopterna) from Kenya with the description of two new species - Wasonga, Domnick V.; Channing, Alan (Zootaxa, 2013)
African sand frogs in the genus Tomopterna presently include 13 species. These are known to be highly cryptic and morphologically similar. Despite increased effort in the recent past, the taxonomy of the group is still unresolved and some populations e.g. in Kenya have remained largely unstudied. This paper starts to address this gap using molecular, advertisement call and morphological comparisons. We test the boundaries of the Kenyan species based on mitochondrial 16S rRNA sequence data. Two new species are recognised and described: Tomopterna wambensis sp. nov. and Tomopterna gallmanni sp. nov. Further molecular and advertisement call studies of Tomopterna populations in Kenya are recommended, especially for those populations previously identified as T. cryptotis and T. tandyi.